2007
DOI: 10.1038/nphoton.2007.96
|View full text |Cite
|
Sign up to set email alerts
|

Actuation of micro-optomechanical systems via cavity-enhanced optical dipole forces

Abstract: We demonstrate an optomechanical system employing a movable, micron-scale waveguide optically-coupled to a high-Q optical microresonator. We show that milliwatt-level optical powers create micron-scale displacements of the input waveguide. The displacement is caused by a cavity-enhanced optical dipole force (CEODF) on the waveguide, arising from the stored optical field of the resonator. The CEODF is used to demonstrate tunable cavity-waveguide coupling at sub-mW input powers, a form of all-optical tunable fil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(170 citation statements)
references
References 40 publications
3
166
0
1
Order By: Relevance
“…Eichenfield et al [23] used the optical gradient force between a tapered optical fiber and a microresonator to pull a movable tapered fiber towards the resonator. An input power of less than 370 μW was used to displace the tapered fiber by about 120 nm.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eichenfield et al [23] used the optical gradient force between a tapered optical fiber and a microresonator to pull a movable tapered fiber towards the resonator. An input power of less than 370 μW was used to displace the tapered fiber by about 120 nm.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…The dipole or gradient force from one microresonator can be used to amplify or dampen the mechanical motion of another microscopic device, such as a nanostring [21] or a microdisk [22], as well as provide a way to precisely control the gap between them [3,4,6,7]. For example, Eichenfield et al [23] have shown how the cavity-enhanced optical dipole force from a microdisk can be used to control the relative position of a movable, tapered optical fiber. Povinelli et al [3] discussed the possibility of observing both positive and negative optical forces between two evanescently coupled microspheres, sometimes termed a "photonic molecule."…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the downscaling of optical systems to the micro and nano-scale resulted in very compliant systems with nanogram-scale masses, rendering them susceptible to optical forces 3,4,5,6 . In fact, optical forces have been exploited to demonstrate chaotic quivering of microcavities 7 , optical cooling of mechanical modes 8,9,10 , actuation of a tapered-fiber waveguide 11 , and excitation of the mechanical modes of silicon nano-beams 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these methods allow for amplification of the optical force per milliwatt of input power, although-locally-the force per milliwatt of optical power remains the same. We mention the so-called resonator-based enhancement and the slow-light enhancement techniques as two examples [88,89].…”
Section: (Iii) Discussionmentioning
confidence: 99%